EVALUASI BAHAN AJAR MATAKULIAH KYOUJUHOU : “PERAN GURU DAN METODE PENGAJARAN BAHASA JEPANG” - Dwi Astuti Retno Lestari; Nia Setiawati; Tia Ristiawati (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
The Japanese Language Education Study Program at State University of Jakarta has designated Japanese language teachers as its graduate profile. To achieve the profile, a series of courses have been prepared, one of which is Nihongo Kyoujuhou that equips students with Japanese language teaching methodology. However, observations of pre-service teaching practices and evaluation of learning outcomes show that students’ teaching skills are still need to be improved. There are some causal factors, one of which is the teaching materials used. Starting from the 2019/2020 academic year, Nihongo Kyoujuhou course use " Peran Guru dan Metode Pengajaran Bahasa Jepang " as teaching material. This research analyzes the textbook with the aim of providing information to study programs and teachers about the effectiveness of the book. The evaluation results show that the textbook " Peran Guru dan Metode Pengajaran Bahasa Jepang " is categorized as very good in terms of language appropriateness and content appropriateness. Meanwhile, the feasibility aspect of presentation is categorized as good. Based on that results, it can be said that this book is suitable to be used as a handbook in the Nihongo Kyoujuhou course. However, the results also show the need for additional books/references to adequately equip students for pre-service teaching practice.